PREVENTION AND CORRECTION OF DISORDERS AND DISEASES OF A VISUAL ORGAN OF MODERN SCHOOL STUDENTS - N. B. Mirskaya; А. D. Sinyakina; А. N. Kolomenskaya (Вопросы современной педиатрии)
High prevalence of pathological conditions of a visual organ at modern school students is the objective medical and social prerequisite for development of the effective measures directed on prevention and correction of disorders and diseases of a visual organ of children of school age. Background: The aim of the study was to establish the prevalence of disorders and diseases of a visual organ at school students for development of the medical and organizational actions directed on their prevention and correction. Patients and methods: The analysis of medical documentation, the extracting from registration forms of the children's policlinics and medical offices of schools, is carried out (1332 extracted sheets of pupils of a primary, middle and advanced school age of basic high comprehensive schools of Moscow). Results: Authors prepared conceptual model on prevention and correction of disorders and diseases of a visual organ of school students for development of the medical and organizational actions directed on prevention of revealed ophthalmopathy. Conclusion: The use of this conceptual model and also its separate structural components is directed on increase of the level of knowledge of medical workers and optimization of their work on identification and reduction of number of risk factors of disorders of a visual organ of pupils of general education institutions. It will allow to carry out work on prevention and correction of the revealed disorders and diseases of a visual organ of school students at better level throughout the entire period of their training at school.